1976
DOI: 10.1111/j.1532-5415.1976.tb04279.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Responses of Men 49 to 65 Years of Age to Endurance Training*

Abstract: A study was made of the effects of training for 30 minutes, three days a week for 20 weeks on certain physiologic measures of sedentary men between 49 and 65 years of age. Twenty-two subjects volunteered for the experimental group, and 8 others for the control group. Exercise sessions were conducted on a quarter-mile track and consisted of continuous bouts of walking and jogging. The average daily energy expenditures progressed from 228 to 365 kilocalories between weeks 4 and 20. For the same period, average e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…When these protocols are adhered to strictly, these continuous-scale measures are reproducible and valid. 9,10 In our view, the advantages of these measures are that they are well-established markers of physical conditioning that are frequently reported in the literature. Functional limitations have been defined as the gap between a person's capabilities and the demands of the environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When these protocols are adhered to strictly, these continuous-scale measures are reproducible and valid. 9,10 In our view, the advantages of these measures are that they are well-established markers of physical conditioning that are frequently reported in the literature. Functional limitations have been defined as the gap between a person's capabilities and the demands of the environment.…”
mentioning
confidence: 99%
“…For impairment in our study, we measured maximal voluntary performance for aerobic capacity and maximal voluntary muscle torque. Aerobic capacity is reported as peak oxygen consumption, 9 and muscle torque is reported as maximal voluntary muscle torque for the quadriceps femoris muscles. 10 Protocols for maximal voluntary performance measures were developed in an effort to isolate the variable of interest-aerobic capacity or maximal voluntary force-and to minimize the influence of other factors.…”
mentioning
confidence: 99%
“…[3][4][5][6] The age-associated decline in maximal oxygen consumption can be attenuated by habitual aerobic exercise, although the mechanism is unclear. [7][8][9][10][11] Although it has been shown that exercise training can augment both cardiac output and the AV oxygen difference in younger subjects, 12,13 these components have not been measured in older subjects before and after exercise intervention.…”
mentioning
confidence: 99%
“…Aging is a natural process characterized by a reduction of the physiological functions and responses, particularly from the third decade of life onwards, when a progressive decline of the functional capacity takes place, the speed of which depends on the individual's genetic factors, health conditions, and lifestyle 1 . Th ese changes caused by aging increase the incidence of cardiovascular disease in both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, women over 50 suff er a decrease in the parasympathetic modulation, and these diff erences tend to lessen with age [11][12][13][14] . Thus, although aging manifests itself in the responses of functional variables, exercise can diminish the consequences of a slower physiological rhythm 1 . Regular exercise, especially aerobic exercise or aerobic physical training (APT), can change the control of the ANS over the CVS, raising parasympathetic activity with or without the reduction of sympathetic activity.…”
Section: Introductionmentioning
confidence: 99%